Association Between Nutritional Adequacy Level and Iron-Folic Acid (IFA) Tablet Consumption with Anemia Incidence in Pregnant Women - Wanda Amelia Putri; Dendy Widianto; Ahmad Hisbullah Amrinanto; Dwikani Oklita Anggiruling; Putu Bunga Fitridewi; Azzahra Nadya Putri (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
Anemia in pregnancy remains a major public health concern due to its adverse effects on maternal and fetal outcomes. Nutritional inadequacy and poor adherence to iron–folic acid (IFA) supplementation are key contributors to anemia among pregnant women in Indonesia. This study aimed to determine the association between nutritional adequacy levels and IFA tablet consumption with anemia incidence in pregnant women. A cross-sectional study was conducted from July to August 2024 at Pulo Armyn Public Health Center, Bogor City, involving 86 pregnant women in their first and second trimesters selected through purposive random sampling. Data were collected using structured questionnaires and 2×24-hour dietary recalls, while hemoglobin levels were obtained from medical records. Statistical analysis employed the Spearman rank correlation test. The results showed no significant association between macronutrient (energy, protein, fat, carbohydrate) and micronutrient (calcium, folate, iron, vitamin C) adequacy levels with anemia incidence (p > 0.05). However, a significant negative correlation was found between adherence to IFA tablet consumption and anemia incidence (p = 0.004; r = –0.311). Pregnant women with good adherence to IFA supplementation exhibited lower anemia prevalence compared to those with poor adherence. These findings underscore the importance of improving adherence to IFA supplementation alongside efforts to enhance dietary quality as part of comprehensive anemia prevention strategies in maternal health programs.